The Relation Ship Between Family Behavior Regarding Bronchial Asthma and Prevention of Bronchial Asthma Recurrence in Community Health Centers Simpang Tiga – Riau - Nurliaty (Jurnal EduHealth, 2022)
Bronchial asthma is a reversible respiratory disease, it does not persist. It can be cured well if treated properly. Recurrence of bronchial asthma does not occur if the trigger factors are avoided. This requires good behavior from the family in caring for patients at home. Behavior regarding bronchial asthma will influence the family in taking action to prevent recurrence of bronchial asthma. This study aims to determine the relationship between family behavior regarding bronchial asthma and measures to prevent recurrence of bronchial asthma. The type of research carried out was correlational with a cross-sectional design. The population in this study were all families of patients suffering from bronchial asthma who received treatment at the Simpang Tiga Health Center - Riau. The sampling technique was accidental sampling technique and a total of 25 respondents were obtained. The research results were analyzed using the Chi Square statistical test. The results of the study showed that the majority of family behavior regarding bronchial asthma was in the adequate category (72%) and the majority of preventive measures taken by families were poor (80%). From the data analysis obtained (P=0.77), this shows that there is no relationship between family behavior and measures to prevent recurrence of bronchial asthma.Behavior does not absolutely influence family actions in caring for family members. So it is recommended that health workers provide repeated counseling to families so that their actions change for the better. From the data analysis obtained (P=0.77), this shows that there is no relationship between family behavior and measures to prevent recurrence of bronchial asthma. Behavior does not absolutely influence family actions in caring for family members. So it is recommended that health workers provide repeated counseling to families so that their actions change for the better. The research results were analyzed using the Chi Square statistical test. The results of the study showed that the majority of family behavior regarding bronchial asthma was in the adequate category (72%) and the majority of preventive measures taken by families were poor (80%). From the data analysis obtained (P=0.77), this shows that there is no relationship between family behavior and measures to prevent recurrence of bronchial asthma